2017
DOI: 10.1021/acs.macromol.6b02685
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Morphology and Dynamics of Polyelectrolyte Brush Condensates in Trivalent Counterion Solution

Abstract: Recent experiments have shown that trivalent ion, spermidine 3+ , can provoke lateral microphase segregation in DNA brushes. Using molecular simulations and simple theoretical arguments, we explore the effects of trivalent counterions on polyelectrolyte brushes. At a proper range of grafting density, polymer size, and ion concentration, the brush polymers collapse heterogeneously into octopus-like surface micelles. Remarkably, the heterogeneity in brush morphology is maximized and the relaxation dynamics of ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 68 publications
(157 reference statements)
5
32
0
Order By: Relevance
“…Depending on the chain stiffness, brush condensates adopt diverse morphological patterns that vary from semi-spherical octopus-like micelle domains to cylindrical bundles of rigid chains which protrude from the grafting surface. It was shown that when the grafting density is in a proper range, multivalent counterions can collapse flexible PE brush even in good solvent into octopus-like surface micelles displaying substantial lateral heterogeneity [42][43][44] , which has recently been confirmed experimentally for polystyrene sulfonate brush condensates in Y(NO 3 ) 3 solution 45 .…”
Section: Introductionmentioning
confidence: 82%
“…Depending on the chain stiffness, brush condensates adopt diverse morphological patterns that vary from semi-spherical octopus-like micelle domains to cylindrical bundles of rigid chains which protrude from the grafting surface. It was shown that when the grafting density is in a proper range, multivalent counterions can collapse flexible PE brush even in good solvent into octopus-like surface micelles displaying substantial lateral heterogeneity [42][43][44] , which has recently been confirmed experimentally for polystyrene sulfonate brush condensates in Y(NO 3 ) 3 solution 45 .…”
Section: Introductionmentioning
confidence: 82%
“…Liu et al. showed that the brush chains collapsed heterogeneously into “octopus‐like” surface micelles within a certain range of grafting density, polymer size, and ion concentration . Jackson et al.…”
Section: Theory Of Polyelectrolyte Brushesmentioning
confidence: 99%
“…[34] Liu et al showed that the brush chains collapsed heterogeneously into "octopus-like"s urface micelles within ac ertain range of grafting density,p olymer size, and ion concentration. [35] Jackson et al demonstrated that, whilst ostensibly forming similarm icellar structures,s olvophobic collapsed brushes and multivalent-ion-collapsed brushes exhibited distinct mechanistic and structural features. [36] By using a combination of AFM, SFA, and MD simulations, Yu et al confirmed that solvophobic and multivalent-ion-inducede ffects work in concert to drivet he strong phase separation of polyelectrolyte brushes, with electrostatic bridging of polyelectrolyte chains playing an essential role in the formation of the lateral structurali nhomogeneities ( Figure 3b).…”
Section: Theory Of Polyelectrolyteb Rushesmentioning
confidence: 99%
“…The scale-dependent relaxation dynamics of the chromatin domain is quantified using the time evolution of intermediate scattering function F k (t) (43,44) calculated at different length scale (∼ 2π/k) ( Fig. 5B).…”
Section: Scale-dependent Chromatin Relaxation Timementioning
confidence: 99%
“…The scale-dependent relaxation dynamics of the chromatin domain is quantified using the time evolution of intermediate scattering function F k (t)(44,45) calculated at different length Effects of active force on chromosome organization and dynamics. (A) MSD of active and inactive loci compared with those under passive condition.…”
mentioning
confidence: 99%